The Effect of Deep Breathing Exercise on Tidal Volume in Pulmonary Tuberculosis Patients at the Main Clinic of Purwokerto Community Lung Health Class A - Zalfa Aistasya Wahyu; Mustiah Yulistiani (UM Purwokerto Press, 2025)
People with pulmonary tuberculosis often experience ventilation disorders due to lung tissue damage, leading to decreased elasticity and increased airway resistance. This condition reduces tidal volume and disrupts gas exchange and oxygenation. One nonpharmacological intervention that can help improve tidal volume is deep breathing exercise, which enhances lung ventilation and oxygenation. This study aimed to analyze the effect of deep breathing exercise on tidal volume in pulmonary tuberculosis patients at the Main Clinic of Purwokerto Community Lung Health Class A. A quasi-experimental design with one group pre-test and post-test was used, involving 28 patients in the intensive phase selected through total sampling. The intervention was conducted for three days. Tidal volume was measured via interactive video calls at the patients' homes using balloons and calculated with the formula V = ?r²t. Each session was measured three times, and the highest value was recorded. The mean tidal volume increased from 2834.32 ml before intervention to 5365.00 ml after. Wilcoxon test results showed a p-value of 0.001, indicating a significant difference. In conclusion, deep breathing exercise is effective in increasing tidal volume in pulmonary tuberculosis patients and can be considered a supportive therapy.